The Influence of Education and Period of Work on Employee Performance in Regional Secretariat Offices Majene District - Nur Qamariah (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This research aims to determine whether education and work experience partially influence employee performance and whether education and work experience simultaneously influence employee performance at the Regional Secretariat of Majene Regency. Because every agency, in carrying out its activities and achieving its goals, is constantly faced with problems both from within and outside the agency. The data used in this research is primary data, which was used by distributing questionnaires to employees of the Regional Secretariat of Majene Regency. The sampling technique in this research used the Slovin formula for 58 employees. The data is processed using a Likert scale as numerical data (numbers). Data collection methods in this research are questionnaires and literature study. The data was processed using SPSS for Windows. The data analysis method used quantitative methods using multiple linear regression analysis.